2018
DOI: 10.2174/1871530318666180605094706
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Transferrin Receptor-1 (CD71) Expression in Acute Lymphoblastic Leukemia

Abstract: 'Positive Transferrin receptor -1 (CD71) expression in patients with ALL is adverse prognostic factor and should be taken in consideration in designing future therapeutic strategies based on patient- specific risk factors'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In fact, TfR1 has been identified as a universal cancer marker (55). Increased expression of TfR1 correlates with advanced stage and/or poorer prognosis in a number of cancers, including solid cancers such as esophageal squamous cell carcinoma (56), breast cancer (57, 58), ovarian cancer (59), lung cancer (60), cervical cancer (61), bladder cancer (62), osteosarcoma (63), pancreatic cancers (64), cholangiocarcinoma (65), renal cell carcinoma (66), hepatocellular carcinoma (67,68), adrenal cortical carcinoma (69), and cancers of the nervous system (70) as well as hematopoietic malignancies such as acute lymphoblastic leukemia (ALL) (71,72), chronic lymphocytic leukemia (CLL) (73), and non-Hodgkin lymphoma (NHL) (73,74). Interestingly, patients infected with the human immunodeficiency virus (HIV) often develop more aggressive NHL that have been shown to express even higher levels of TfR1 messenger RNA compared to NHL cells from non-infected patients (75,76).…”
Section: Tfr1 Expression In Normal and Cancer Cellsmentioning
confidence: 99%
“…In fact, TfR1 has been identified as a universal cancer marker (55). Increased expression of TfR1 correlates with advanced stage and/or poorer prognosis in a number of cancers, including solid cancers such as esophageal squamous cell carcinoma (56), breast cancer (57, 58), ovarian cancer (59), lung cancer (60), cervical cancer (61), bladder cancer (62), osteosarcoma (63), pancreatic cancers (64), cholangiocarcinoma (65), renal cell carcinoma (66), hepatocellular carcinoma (67,68), adrenal cortical carcinoma (69), and cancers of the nervous system (70) as well as hematopoietic malignancies such as acute lymphoblastic leukemia (ALL) (71,72), chronic lymphocytic leukemia (CLL) (73), and non-Hodgkin lymphoma (NHL) (73,74). Interestingly, patients infected with the human immunodeficiency virus (HIV) often develop more aggressive NHL that have been shown to express even higher levels of TfR1 messenger RNA compared to NHL cells from non-infected patients (75,76).…”
Section: Tfr1 Expression In Normal and Cancer Cellsmentioning
confidence: 99%
“…The systematic iron pool in patients with leukemia is also increased, which is aggravated by multiple red-blood-cell transfusions. Multiple experimental and epidemiological studies have demonstrated the relationship between dysregulation of iron metabolism with the occurrence and progress of leukemia [911].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, poorly differentiated primary AML blasts tend to express higher levels of TfR1 than partially differentiated AML blasts [52]. TfR1 expression is higher in patients with T-cell ALL than patients with B-cell ALL [11, 54]. Clinical analysis also shows that overexpression of TfR1 in ALL is an adverse prognostic factor [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the current tumor staging systems fails to adequately predict the prognosis of numerous cancers, underlying the need for urgent identification of biomarkers for accurate tumor diagnosis and prognosis. Growing evidence shows that aberrant iron metabolism participates in AML initiation, progression, and infiltration of immune cells to the microenvironment (Kennedy et al, 2014;Benadiba et al, 2017;Hagag et al, 2018). Numerous studies have implicated dysregulated expression of IMRGs in cancer progression (Li et al, 2020;Zhu et al, 2021;Song et al, 2022).…”
Section: Discussionmentioning
confidence: 99%